The Influence of the Human Factor on Vigilance in Driving - Buriak, S. Y; Gololobova, O. O; Serdiuk, T. M; Afanasov, A. M; Skalko, V. V; Yamburh, K. O; Bilukhin, D. S (Science and Transport Progress, 2022)
Purpose. The purpose of this study is to find ways to improve the system for monitoring and controlling the human condition, which is directly involved in driving vehicles, by borrowing knowledge and achievements from the field of scientific research in matters related to determining a person's response to the action of various factors of influence, irritating factors, interaction with other people and technical means, the ability to maintain long-term ability to work, etc. Methodology. Since transportation requires both high professional and personal skills, it is necessary to develop and implement systems for monitoring and controlling the human condition that would meet the needs of the achievements of the modern level of technical development. To determine the factors of influence on a person, an analysis of research in this area was conducted. Findings. It is emphasized that each person has, firstly, his or her own peculiarities, and secondly, cannot be in two identical states at different times. Given these and other aspects, a universal approach should be developed to determine and verify a person's responsibility for making relevant decisions. The main factors influencing the driver's attention are identified. Among them, in addition to the physiological one, the psycho-emotional state takes a significant place, which also needs to be taken into account. Originality. The development of technology leads to new needs and provides new opportunities in almost all industries. One of these is the study of humans. The proposed approach allows us to take a broader look at the role and place of a person, his or her integration into the transportation process. Practical value. The analysis of the forms of influence and types of load on different systems of human perception made it possible to outline the task of determining the ability of a person to act responsibly under the influence of significant factors.